Thickening of iron ore tailings slimes using sub-aerial deposition: field experimental observations - Oliveira-Filho, W.L.; Silva, D.R.; Almeida, F.E. (Paste 2013: Proceedings of the 16th International Seminar on Paste and Thickened Tailings, 2013)
This paper describes a field experiment of sub-aerial deposition of iron ore tailings slimes to study shrinkage characteristics of tailings under conditions of surface drying and lowered ground water level. The paper outlines site conditions and features of the test and describes instrumentation setup in detail. Material behaviour and climatic conditions were monitored during the desiccation process by a set of soil sensors and a weather station. Progress of water volumetric content, solids content, dry density, and gravimetric water content of soil during desiccation are presented, and the paper points out an efficient method to improve material properties. Crack formation and evolution over time is also described using photographs. Finally, there is a brief account of numerical modelling, which is compared with field data.